Design guideline for CO2 to methanol conversion process supported by generic model of various bed reactors. (1st October 2022) - Dat Vo, Nguyen; Oh, Min; Lee, Chang-Ha
Highlights: Performance of CO2 -to-methanol process was evaluated using various reactors. Competitive reactors, optimal conditions, and order of uncertainty parameters were presented. A design guideline for the CTM process was suggested under vision up to 2050. Green methanol can be produced at a competitive cost with the maximum of −0.83 kgCO2 /kgMeOH. The results are useful for the CTM and other chemical processes using bed reactors. Abstract: This study developed a novel design guideline for CO2 to methanol (CTM) conversion process supported by a generic model for various types of bed reactors (BRs) as the process economics depends on BR selection. Using commercially feasible BRs, such as fixed bed (FxB), bubbling fluidized bed (BFB), turbulent fluidized bed (TFB), and fast fluidized bed (FFB), we analyzed the CTM process to determine the optimum recycle ratio, gas velocity over the minimum fluidization velocity (GV/MFV) ratio, inlet reactor pressure, and inlet reactor temperature. At full recycle of unconverted gas, the optimum GV/MFV ratio was 0.1 for the process using an FxB reactor, while conversion using a TFB reactor was a better option than those using BFB and FFB reactors at the GV/MFV ratio of 7.03. Meanwhile, the CTM process using various types of BRs performed the minimum cost at 55 bar for reactor pressure and 498 K for reactor temperature. Owing to the competitiveness of the FxB and TFB reactors at small and large CO2 source rates, respectively, further analysis of the optimal conditions was conducted for these reactors, and a design guideline for the CTM process using these reactors was developed. The effect of the uncertainty parameters on the process design was analyzed to determine the CO2 source rate, green H2 cost, and CO2 cost. The design guideline was suggested for proper CTM process at different uncertainty values of CO2 source rate and material costs under a vision up to 2050 (for net-zero emissions). Finally, the design guideline integrated with methanol purifiers highlighted its reliability for high-purity methanol production. The production cost (∼340 $/tMeOH at 2050) for green methanol (mitigated −0.78 to −0.83 kgCO2 /kgMeOH) was highly competitive with the cost (310 to 520 $/tMeOH) of traditional methanol production emitted 1.6 to 2.971 kgCO2 /kgMeOH. The developed guidelines are useful for the design, operation, and decision-making of the CTM process. In addition, the developed models for BRs can contribute to other CO2 utilization processes.